The collective online shopping system: The impact of the effectiveness for the Portuguese business partners - Colaço, Filipa; Laureano, L.; Laureano, Raul M. S.; Ferreira, P. A. (2018 13th Iberian Conference on Information Systems and Technologies (CISTI), 2018)
Globalization and the emergence of the internet have significantly influenced the creation of new business models where the main goal is to effectively and efficiently implement strategies to surpass clients' expectations. The collective online shopping systems emerge in 2008, and may be considered as an effective promotion tool for business partners. In this context, the main goal of this research paper is to evaluate the perception of the business partners on the effectiveness of the last promotional campaign made using a collective online shopping system. Additionally, it is also analysed the consequents of effectiveness. The sample is comprised of 38 global business partners. The results lead to the following conclusions. First, the global effectiveness of the campaigns tends to be positive, mainly due to the non-financial effectiveness. Second, the global and non-financial effectiveness are predictors of their consequents, namely: word-of-mouth marketing, image, returning customers, customer retention, repeat the promotion and recommend promotion, while the financial effectiveness has no influence on any consequent. The existing literature on collective online shopping systems is still scarce. This research contributes to the literature by analysing the effectiveness and identifying the consequents of the effectiveness. From a business perspective, this study may help business partners to evaluate the impact on their business from promotional campaigns using collective online shopping sites and make a decision whether to join or not. From the site managers' perspective, this study may contribute to a better understanding of the perception held by the business partners on the business model's effectiveness and how to better meet their objectives.